Spatial-temporal of fire foci in the state of Rio de Janeiro, Brazil (Bioscience Journal, 2020)
This study evaluated the space-time variability of fire foci via environmental satellites for the State of Rio de Janeiro (SRJ) based on statistical procedures. The fire foci in the period of 2000 to 2015 were obtained from the BDQueimadas fire database. Descriptive, exploratory, and multivariate statistical analyses were performed in the software environment R i386 version 3.2.5. The north region had 6760 foci (21.11%), the south-central region had 3020 foci (9.43%), the Middle Paraíba had 6,352 foci (19.84%), the Metropolitan areas had 6671 foci (20.83%), and the Green Coast region had 292 foci (0.91%). The cluster analysis identified three homogeneous groups of fire foci (G1, G2, and G3) but did not include the municipality of Campos dos Goytacazes (NA). The G1 group (6.21 ± 0.01 foci, 57.61%) included areas throughout the state and covered the coastal region and lowlands towards the north. The G2 group (6.21 ± 0.01 foci, 34.81%) included the northern, south-central, and coastal shallows regions. The G3 group (6.21 ± 0.01 foci, 9.78%) included the mountain ranges of the state. Environmental characteristics and socioeconomic are crucial in the dynamics of fire foci in Rio de Janeiro.